What grandparents mean to grandchildren - Aliling, Evelyn Pangilinan
This study investigated what grandparents mean to their grandchildren.Conducted in December 1986, it answers the following questions: 1) What grandparents do for their grandchildren, 2) What grandchildren feel about their grandparents, 3) What grandchildren like most about their grandparents, 4) What grandchildren dislike most about their grandparents, 5) Are there significant differences in the meanings grandchildren hold for their grandparents when they (grandchildren) are grouped by sex and socio-economic status? The study was participated in by sixty (60) purposively selected 5-year old children from two socio-economic groups: the high SES from PG nursery School in Tomas Morato, Quezon City, and the low SES from Barangay Pinahan, in Kamias, Quezon City. Computing for the percentage, means, standard deviations, and t-values, results showed that there was no significant difference in he meanings of grandchildren hold for their grandparents by SEX and SES of the grandchildren. Analysis of the findings likewise indicated that 1) majority of the grandparents play with their grandchildren; 2) most grandchildren feel love toward their grandparents; 3) grandchildren generally like most being cared for by their grandparents; 4) grandchildren hardly have anything they dislike about their grandparents.